The Involvement of Renal Capsule Is Associated With Acute Kidney Injury in Patients With Acute Pancreatitis - Wei, Mei; Zhang, Jingzhu; Qu, Cheng; Liu, Yang; Gao, Kun; Zhou, Jing; Ke, Lu; Tong, Zhihui; Li, Weiqin; Li, Jieshou (Frontiers in Medicine, 2021)
Background: Acute pancreatitis (AP) is characterized by pancreatic/peripancreatic inflammation. Involvement of renal capsule refers to peripancreatic inflammation extending beyond the Gerota fascia and disappearance of renal rim sign (+) on CT images. However, its association with acute kidney injury (AKI), an important complication of AP, was rarely studied. Aim: This study aimed to assess the relationship between the involvement of renal capsule and AKI in a cohort of patients with AP. Methods: We retrospectively screened all the patients admitted for AP from January 2018 to December 2019. The involvement of renal capsule was judged by experienced radiologists according to the CT imaging. Propensity score matching (PSM) was used to control for biases in group sizes and baseline characteristics. The primary outcome was the development of AKI during the index admission. We also categorized the pararenal inflammation with the renal rim grade (RRG) and compared the incidence of AKI among different grades. Results: Involvement of renal capsule was identified in 71 of 503 patients (14.1%). The incidence of AKI was significantly higher in these patients when compared with the matched controls (43/71, 60.6% vs. 12/71, 16.9%, p < 0.001). Moreover, mortality also differed between groups (12.7% vs. 1.4%, p = 0.017). Multivariable logistic regression showed that renal capsule involvement is an independent risk factor of AKI (odds ratio, 4.355; 95% confidence interval, 1.434, 13.230, p = 0.009). Patients with RRG grade III had a significantly higher incidence of AKI than the other two grades (60.6% for Grade III, 17.1% for Grade II, and 3.8% for Grade I, p < 0.001). Conclusion: Involvement of renal capsule is associated with higher AKI incidence and mortality.